Effect of referral systems on costs and outcomes after hip fracture surgery in Taiwan. (18th September 2020) - Chiou, Bo-Lin; Chen, Yu-Fu; Chen, Hong-Yaw; Chen, Cheng-Yen; Yeh, Shu-Chuan Jennifer; Shi, Hon-Yi
Abstract: Objective: To explore the economic burdens of hip fracture surgery in patients referred to lower-level medical institutions and to evaluate how referral systems affect costs and outcomes of hip fracture surgery. Design: A nationwide population-based retrospective cohort study. Setting: All hospitals in Taiwan. Participants: A total of 7500 patients who had received hip fracture surgery (International Classification of Disease, 9th Revision, Clinical Modification (ICD-9-CM) diagnostic codes 820.0 ∼ 820.9 and procedure codes 79.15, 79.35, 81.52, 81.53) performed in 1997 to 2013. Main outcome measures: Total costs including outpatient costs, inpatient costs and total medical costs and medical outcomes including 30-day readmission, 90-day readmission, infection, dislocation, revision and mortality. Results: The patients were referred to a lower medical institution after hip fracture surgery (downward referral group) and 3034 patients continued treatment at the same medical institution (non-referral group). Demographic characteristics, clinical characteristics and institutional characteristics were significantly associated with postoperative costs and outcomes ( P  < 0.05). On average, the annual healthcare cost was New Taiwan Dollars (NT$)2262 per patient lower in the downward referral group compared with the non-referral group. The annual economic burdens of the downward referral group approximated NT$241 million (2019 exchange rate, NT$30.5 = US$1). Conclusions: Postoperative costs and outcomes of hip fracture surgery are related not only to demographic and clinical characteristics, but also to institutional characteristics. The advantages of downward referral after hip fracture surgery can save huge medical costs and provide a useful reference for healthcare authorities when drafting policies for the referral system.